Analysis of Big Data Potential in Zakat Fund Management and Transparency in the Digital Era at BAZNAS Riau - Muhammad Dandi Kurnia; Wilaela Wilaela; Saifullah Saifullah (al-Afkar, Journal For Islamic Studies, 2026)
Advances in digital technology have driven transformations in the governance of zakat management institutions, including the National Zakat Agency (BAZNAS), which are necessary to improve the effectiveness and transparency of zakat fund management. This study aims to analyze the potential use of big data to support the management and transparency of zakat funds in the digital era at BAZNAS, Riau Province, and to identify challenges and implementation strategies. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis related to zakat information systems and management. The results show that big data has significant potential to improve the accuracy of zakat potential mapping, optimize fundraising and distribution, and enhance transparency and accountability through a publicly accessible, real-time digital reporting system. However, its implementation has not been fully optimal due to limitations in technological infrastructure, data integration between institutions, and human resource capacity in data analysis. Therefore, strengthening technological infrastructure, improving human resource competency, integrating data systems, and strengthening data governance and policies are essential. The contribution of this research lies in providing an empirical analysis of the strategic role of big data in zakat management at the regional level, particularly in the context of the digital transformation of zakat institutions. This research also provides a conceptual framework for integrating big data into the zakat management system, emphasizing transparency, accountability, and institutional efficiency. Furthermore, the findings can serve as a practical reference for zakat management institutions, particularly BAZNAS (National Agency for the National Development Planning Agency) in various regions, in designing strategies for utilizing digital technology to sustainably improve the quality of zakat governance. This study concludes that optimizing big data can promote more transparent, accountable, and sustainable zakat management in the digital era.